Montreal 1976 to Sydney 2000 The Australian Experience - Nugent, L. (2nd International Forum on Elite Sport. Barcelona, Centre d'Alt Rendiment (C.A.R.) de Catalunya, 11-13 September 2001, 2001)
Strategic Implementation - Institutes and Academy of Sport - The Club program - Sport Science and Sport Medicine - Development of Coaching Expertise - The National Event Program - International Competition - Financial Incentive Programs - Media Profile - The National Youth Program - The Don Talbot Factor